Bochica, variedad mejorada de trigo de altos rendimientos para el altiplano cundiboyacense. - Coca Cadena, A.; Sierra Daza, J.; Delgado M, J.; Brito Molina, R. (Instituto Colombiano Agropecuario, 2018)
Trigo-Triticum aestivu